Assembly of polyethyleneimine in the hexagonal mesophase of nonionic surfactant: effect of pH and temperature - Sharma, Kamendra P.; Choudhury, Chandan Kumar; Srivastava, Sonal; Davis, Hilda C.; Rajamohanan, P. R.; Roy, Sudip; Kumaraswamy, Guruswamy (Journal of Physical Chemistry B, 2011)
We investigate the dispersion of a pH responsive polymer, polyethyleneimine, PEI, in a hexagonal (H(1)) mesophase of a nonionic surfactant, C(12)E(9), and water, at pH ranging from basic (pH = 12.8) to acidic (pH = 1). While the C(12)E(9)/H(2)O phase behavior is independent of pH, we demonstrate that, in the PEI/C(12)E(9)/H(2)O system, changing the pH influences PEI-C(12)E(9) interactions, and thus, influences the isotropic-H(1) phase transition. With decrease in pH, there is increasing protonation of the PEI chain, and consequently, the chain extends. We show, using a combination of SAXs, optical microscopy and visual experiments, that the inclusion of PEI in a 1:1 surfactant water mixture, lowers the hexagonal-isotropic transition temperature, T. At higher pH = 12.8 T(HI) shows a pronounced decrease from SO to 13 degrees C on addition of PEI, and the PEI/C(12)E(9)/H(2)O system forms a transparent gel. At pH = 1, we observe qualitatively different behavior and an opaque gel forms below T(HI)= 25 degrees C. The isotropic-H(1) transition, in turn, influences the phase separation of PEI chains from the C(12)E(9)/H(2)O system. 2D NMR ROESY data provides evidence that there are strong surfactant PEI interactions at high pH that significantly reduce at lower pH. The NMR data is in accord with molecular dynamics simulations that show that surfactants strongly aggregate with unprotonated PEI chains, but not with fully protonated chains; thus, in this system, the pH controls a cascade of microstructural organization: increasing pH decreases chain protonation and increases polymer-surfactant interactions, resulting in suppression of the isotropic-H(1) transition to lower temperatures, thus, influencing the phase separation of PEI from the surfactant/water system.

Unusual conformational similarity of two peptide folds featuring sulfonamide and carboxamide on the backbone - Vijayadas, Kuruppanthara N.; Davis, Hilda C.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
Two folded peptides featuring carboxamide and sulfonamide at the core of the peptide fold have been shown to possess almost similar conformational features, despite the well-known fact that carboxamides and sulfonamides have strikingly different hydrogen-bonding and geometrical preferences.

Ant-pro reverse-turn motif. structural features and conformational characteristics - Thorat, Vijaykumar H.; Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Kale, Sangram S.; Ramesh, Veera V. E.; Davis, Hilda C.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; et al. (European Journal of Organic Chemistry, 2013)
This article details the characteristic conformational features of the Ant-Pro reverse turn ? a folded pseudo -turn motif that displays a closed nine-membered-ring hydrogen-bonded network involving just two amino acid residues, namely anthranilic acid (Ant; a constrained -amino acid), and proline (Pro; a constrained -amino acid). The results from the extensive investigation of ten crystal structures and their NMR conformations in the solution state provide a clear idea about the conformational characteristics of the Ant-Pro reverse turn. The Ant and Pro residues, which form the turn segment, maintain a perfect antiperiplanar orientation throughout, leaving little possibility for the formation of the otherwise possible six-membered hydrogen-bonding that requires a coplanar disposition of the two amino acid residues, as clearly evident from investigation of several crystal structures. The closed hydrogen-bonded network observed in the Ant-Pro reverse turn motif, formed in the forward direction of the sequence (12 amino acid interactions) involving only two amino acid residues, is in stark contrast to the native -turns that involve four residues to form hydrogen-bonded network featuring backward 14 amino acid interactions. The readily available two-residue Ant-Pro motif raises the possibility of a practical utility, particularly in the application of rigidifying flexible peptide backbones by inserting the robust Ant-Pro reverse turn motifs into their backbone.
Keywords: Peptides; Peptidomimetics; Protein folding; Protein structures